Curcumin-Functionalized Graphene Oxide Strongly Prevents Candida parapsilosis Adhesion and Biofilm Formation - Cacaci, Margherita; Squitieri, Damiano; Palmieri, Valentina; Torelli, Riccardo; Perini, Giordano; Campolo, Michela; Di Vito, Maura; Papi, Massimiliano; Posteraro, Brunella; Sanguinetti, Maurizio; Bugli, Francesca (Pharmaceuticals (Basel, Switzerland), 2023)
Candida parapsilosis is the major non-C. albicans species involved in the colonization of central venous catheters, causing bloodstream infections. Biofilm formation on medical devices is considered one of the main causes of healthcare-associated infections and represents a global public health problem. In this context, the development of new nanomaterials that exhibit anti-adhesive and anti-biofilm properties for the coating of medical devices is crucial. In this work, we aimed to characterize the antimicrobial activity of two different coated-surfaces, graphene oxide (GO) and curcumin-graphene oxide (GO/CU) for the first time, against C. parapsilosis. We report the capacity of GO to bind and stabilize CU molecules, realizing a homogenous coated surface. We tested the anti-planktonic activity of GO and GO/CU by growth curve analysis and quantification of Reactive Oxigen Species( ROS) production. Then, we tested the antibiofilm activity by adhesion assay, crystal violet assay, and live and dead assay; moreover, the inhibition of the formation of a mature biofilm was investigated by a viability test and the use of specific dyes for the visualization of the cells and the extra-polymeric substances. Our data report that GO/CU has anti-planktonic, anti-adhesive, and anti-biofilm properties, showing a 72% cell viability reduction and a decrease of 85% in the secretion of extra-cellular substances (EPS) after 72 h of incubation. In conclusion, we show that the GO/CU conjugate is a promising material for the development of medical devices that are refractory to microbial colonization, thus leading to a decrease in the impact of biofilm-related infections.